(untitled) (American Journal of Islam and Society, 1994)
The three-day seminar on “Islam and Modernity” was held under the joint auspices of the Goethe Institute (Karachi), the International Institute of Islamic Thought (Islamabad), and the Islamic Research Institute (Islamabad). Thirty scholars from Pakistan and four scholars from Germany participated as delegates, and an equal number of other scholars, journalists, and bureaucrats attended as observers. The seminar addressed four themes: a) The State: Legitimation and Participation; (b) The Law: Law and Justice; (c) The Economy and Finance: Economy and Ethics; and (d) Society: Equality and Justice. The sesions were arranged to give adequate time to the presenters and for follow-up discussion. In general, the seminar sought to create a better understanding and appreciation of the current self-assertion in the Muslim world and the ways in which Muslims are dealing with modernity. There is a growing belief among Muslims that it is possible to achieve developmental goals, as well as those of material and social welfare, within the framework of Islam. This, it is believed, would save their societies from moral degradation, the breakdown of social and family structures, the dehumanization of human life, and other negative features of western modernity. This resurgence often generates fear and apprehension in the West, a reaction that might be partially due to sporadic acts of violence by Muslim extremists. The West’s perception of Islamic resurgence is thus colored, which undermines its ability to see it for what it really is. Despite this, however, many people in the West feel the need for a better understanding of the changes taking place in Muslim societies and for entering into a dialogue with their Muslim counterparts in order to explore the possibility of promoting mutual respect and creating an atmosphere of meaningful and peaceful coexistence. In addition to the general divide between Islam and the West, there is a secular vs. Islamist divide within Muslim societies. Some adhere to the secular view of life and seek to confine religion to a private concern, while others want to restructure the individual and all elements of social life according to Islamic principles and values ...